2015
DOI: 10.1002/eat.22381
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, emotional, and situational context of purging episodes in anorexia nervosa

Abstract: Objective The current study examined behavioral, emotional, and situational factors involved in purging among women with anorexia nervosa (AN). Methods Women with AN (n=118) completed a two-week ecological momentary assessment protocol involving daily reports of eating disorder behaviors, mood, and stressful events. Generalized estimating equations examined the likelihood and context of purging following eating episodes involving both overeating and loss of control (binge eating; BE); loss of control only (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…After examining the individual effect of each of the predictors on risk of insulin restriction, we entered all predictors simultaneously to determine which characteristics of the eating episode remained significant after statistically controlling for the other characteristics. Although characteristics of the eating episode are likely related (e.g., eating a large amount of food may be associated with more guilt), conceptually they are distinct and may provide unique targets for intervention ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…After examining the individual effect of each of the predictors on risk of insulin restriction, we entered all predictors simultaneously to determine which characteristics of the eating episode remained significant after statistically controlling for the other characteristics. Although characteristics of the eating episode are likely related (e.g., eating a large amount of food may be associated with more guilt), conceptually they are distinct and may provide unique targets for intervention ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…A review of ecological momentary assessment (EMA) designs showed that momentary increases in NA prospectively predicted DEBs, including purging (Engel et al, 2013; Goldschmidt et al, 2013, 2015), dietary restriction (Berg et al, 2013; Fitzsimmons‐Craft, Ciao, & Accurso, 2016; Selby et al, 2015), loss of control eating (Berg et al, 2013; Engel et al, 2013; Goldschmidt et al, 2012; Ranzenhofer et al, 2014), laxative misuse (Selby et al, 2015), and excessive exercise (Selby et al, 2015). Although previous studies hypothesized that NA mediates the effect between ED‐salient content viewing and DEBs (Griffiths et al, 2018; Tylka & Subich, 2004), this has yet to be tested empirically.…”
Section: Introductionmentioning
confidence: 99%
“…The functions of ED behavior have not been studied as extensively as those of NSSI, and there is little research on possible psychological mechanisms beyond emotion regulation or weight loss/thin ideal and body image dissatisfaction (Lavender et al, ; Rodgers, McLean, & Paxton, ). The existing literature indicates that ED behaviors do serve emotion regulation functions by providing a way to feel a sense of control over one's body, emotions, and cognitive states (Goldschmidt et al, ; Lavender et al, ). Earlier work by Nordbo, Espeset, Gulliksen, Skarderud, and Holte () proposed eight functions for anorexic behaviors: feeling a sense of security and stability, eliciting care from others, demonstrating mental strength, feeling worthy of self‐confidence, establishing a new identity, avoiding negative emotions, communicating difficulties, and wishing to starve to death.…”
Section: Introductionmentioning
confidence: 99%